Morphology and mechanical properties of MIM feedstock using TPNR backbone binder - Hassan, Norita; Sahrim, Ahmad; Muhamad, Norhamidi; Omar, Mohd Afian; Hassan, Noor Azlina (Trans Tech Publications, Switzerland, 2015)
This study has examined the effects of using TPNR backbone polymer on the morphology and mechanical properties of the metal injection moulding feedstock 316L stainless steel with paraffin wax (PW) and palm stearin (PS) respectively as the main binder and stearic acid as a lubricant during mixing and injection moulding process. Tensile behaviour indicates that the green sample of feedstock PW/TPNR/SA system gives higher value compared to PS/TPNR/SA system. Morphology studies showed that green samples of PS/TPNR/SA exhibited brittleness fracture compared to PW/TPNR/SA system.